Womeńs social movements and their consolidation as interlocutors and political actors in the construction of peace in Medellín, Colombia [Los movimientos sociales de mujeres y su consolidación como interlocutor y actor político en la construcción de la paz en Medellín, Colombia] (2017)
The article analyzes the role played by womeńs social movements in the demand for justice within the Colombian conflict, placing them as recognized actors in the political arena for the defense of human rights, as well as a focus of counter-power. Applying a gender perspective, we studied the communicative strategies that have given legitimacy to two associations, namely: "Mothers of Candelaria" and "Women Walking for Truth", both located in Medellín, Colombia.